Implementasi Nilai-nilai Profetik dalam Komunikasi Kelompok di Komunitas Ruqu’ Bandung - Nurhasanah, Nunung (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2017)
This research discusses the implementation of prophetic values by the Ruqu' Community (Rumah Quran Utrujah) in Bandung using a phenomenological method. Three core values of prophetic communication explored are humanization, liberation, and transcendence. The findings show that: first, humanization is realized through mutual respect among members and valuing differing opinions. Second, liberation is realized through a solution-oriented communication approach that helps members overcome challenges. Third, transcendence is realized through enhancing members' ability to read the Quran, which is seen as a form of goodness and piety. Transcendence encompasses not only worldly improvement but also spiritual growth, with a focus on love for the Quran as a manifestation of love and piety towards Allah SWT. Keywords : Prophetic communication; group communication; Komunitas Ruqu’